Associação entre o número de sessões na realização da técnica utilizando o dilatador vaginal EPI-NO® com desfechos intraparto, nível de desconforto e função da musculatura do assoalho pélvico - Santos, Beatriz Laryssa de Jesus (Universidade Federal de São Carlos, 2020)
Introduction: The pelvic floor is located in the lower part of the abdominopelvic cavity and has several important functions of support, continence and allows for physiological sexual intercourse and childbirth. Pregnancy, labor and delivery are factors that can damage pelvic support. Thus, techniques that aim to prepare the musculature, such as the use of Epi-No® vaginal dilator are required. Objective: To verify whether there was an association between the number of sessions in performing the technique using the Epi-No® vaginal dilator with intrapartum outcomes, level of discomfort and pelvic floor muscle function. Methods: An experimental study was carried out with 20 participants, with gestational age between 30 and 34 weeks. Anamnesis and evaluation of the PFM function was performed before and after delivery. The Epi-No® was made available to be used at home, every day, until delivery. Data were tabulated in EXCEL and analyzed in the SPSS program version 20; the variables (pelvic floor muscle function, intrapartum outcomes, satisfaction with the technique) were analyzed by descriptive techniques (mean ± standard deviation, frequency) and the association between the number of sessions (days) of use of Epi-No® and the other variables were analyzed using Fisher's exact test, with a significance level of 5%. Results: There was no association between the number of days performed and the technique in PFM function, intrapartum outcomes and level of satisfaction with the technique. Conclusion: Although the number of sessions performed with the Epi-No® did not interfere with the PFM function or the variables (pelvic floor musculature function, intrapartum outcomes, satisfaction with the technique), the study showed that the use was more frequent. technique, can promote greater chances of presence of intact perineum.
Associação entre o número de sessões na realização da técnica utilizando o dilatador vaginal EPI-NO® com desfechos intraparto, nível de desconforto e função da musculatura do assoalho pélvico
Keywords: Musculatura do Assoalho Pélvico; Parto; Epi-No®; Gestação; CIENCIAS DA SAUDE::MEDICINA::SAUDE MATERNO-INFANTIL